A history of South Africa - Thompson, Leonard Monteath (Yale Nota bene., 2001)
"A leading scholar of South Africa provides a fresh and penetrating exploration of that country's history, from the earliest known human inhabitation of the region to the present, focusing primarily on the experiences of its black inhabitants. For this third edition, Leonard Thompson adds two new chapters that describe the transfer of power and the new South Africa under the presidencies of Nelson Mandela and Thabo Mbeki."--